Perceived Organizational Support, Collegiality, and Teacher Efficacy of Novice Social Studies Junior High School Teachers: The Problems They Faced and Solutions - I-Wen Huang; Chia-Wei Tang (National Taipei University of Education, 2019)
This study aims to look into the relationship among novice social studies field teachers' perceived organizational support, collegiality, and teacher efficacy in Junior High School context and their perception of the workplace challenges and corresponding solutions. The data was collected using interview and survey methods. Valid survey data was collected from 120 social studies teachers, among which 12 teachers were interviewed. The main findings can be summarized as follows: 1) Collegiality partially mediates the relationship between teachers' perceived organizational support and teacher efficacy; 2) the challenges of novice social studies teachers are not the same as those of other subject areas teachers and it takes the school administration, novice teachers and their colleagues altogether to overcome the hurdles. Based on the findings, suggestions are provided for educational administration authority, school leaders, novice social studies teachers and for future studies.